Uzupełnianie dochodów jednostek samorządu terytorialnego środkami z budżetu państwa w krajach europejskich - wybrane problemy - Olejniczak, Jarosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The tendency to decrease role of the intergovernmental transfers is noticed in European countries. The scale of self-government own revenues is rising. There is the strong emphasis placed upon the self-financing of local government, particularly through the use of local taxes. Despite this level of self-financing those own revenues are usually insufficient to cover all expenditures. Most countries begin to prefer unconditional or general grants to arise independence of local and regional self-government. The aim of this analysis is to compare the main goals and ways of redistribution of public money among local governments in different European countries. The main reasons of intergovernmental transfers are vertical and horizontal imbalance, promotion of standard delivery public service, equalization or reimbursement of public spending., stability of revenues, predictability of revenues, comprehensibility, efficiency/cost effectiveness. There are many factors that are determining achieving those goals - such as expenditure needs, resource or needs equalization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 320-331